Antibacterial Activity of Red Galangal (A. purpurata) Extract on the Growth of E. tarda Bacteria - Desy Amalia Hidayati; Arief Prajitno; Titik Dwi Sulistyawati; Giri Pratama; Tania Nilakandhi (Journal of Aquaculture and Fish Health, 2023)
This study aimed to analyze the antibacterial activity of red galangal extract (Alpinia purpurata) against the growth of E. tarda. This aims of this study was to determine the antibacterial compounds and the antibacterial effectiveness of red galangal extract (A. purpurata) against the growth of E. tarda bacteria. Antibacterial activity test was carried out by MIC test and disc test. The MIC test used doses of 1 ppm, 10 ppm, 100 ppm, 500 ppm, and 1000 ppm with incubation for 24 hours. The disc test used doses of 100 ppm, 200 ppm, 300 ppm, 400 ppm, 500 ppm and a positive control of 5 ppm chloramphenicol and a negative control without treatment. Photochemical test of red galangal extract (A. purpurata) contains flavonoid compounds, alkaloids, tannins, triterpenoids, and saponins. The results of the disc test showed that the highest inhibitory diameter was 7.55 mm at a dose of 500 ppm and was bacteriostatic because it decreased its inhibitory zone after 48 hours of incubation. The highest inhibitory effectiveness was 56.56% at a dose of 500 ppm after 24 hours of incubation.